Quality assured full-waveform inversion: Ensuring starting model adequacy - Shah,N; Warner,M; Nangoo,T; Umpleby,A; Stekl,I; Morgan,J; Guasch,L (2012)
Successful full-waveform inversion (FWI) of 3D seismic data typically requires low-frequency content in the field data coupled with an accurate starting velocity model. In these circumstances, two fundamental questions always arise: (1) is the starting model sufficiently accurate given the data that are available, and (2) will the inversion iterate towards the global minimum, or will it instead become trapped locally leading to an erroneous final model? We present a robust and objective means to answer both these questions. The diagnostic feature that we use to achieve this is the spatial continuity of the phase difference between the predicted and observed field data, extracted at a single low frequency, after windowing in time around early arrivals. We show proof of principle on a simple 2D synthetic example, and demonstrate the application of quality assured full-waveform inversion (QA-FWI) to a full 3D field dataset that shows significant velocity anisotropy.